Analisa Ilmu Arudh dan Qawafi dalam Syair al-I’tirof Karya Abu Nawas / An Analysis of Arudh and Qawafi Sciences in The Poem of Al-I’tirof by Abu Nawas - Mochamad Sulthoni Faizin; Ayu' Atisah (Diwan : Jurnal Bahasa dan Sastra Arab, 2020)
درس هذا البحث عن شعر الإعتراف لأبي نواس من من ناحية علوم العروض والقوافي.  هذا الشعر شعر تقليدي الذي لا ينفصل عن قواعد العوارض والقوافي . علم العروض والقوافي هما قواعدان كلاسيكيتان لتحليل الشعر او القصيدة يتم توحيدها عندما لا تتوافق الشعر مع هذه القاعدة العلمية، ثم يُعتبر أن الشعر فاسد أو صحيح . نتائج التحليل في علم العروض ستنتج بحرا، زحافا ، وعلة يستخدمه الشعراء في شعر.  وتحليل علم القوافي سينتج أشكال قافية وأنواع قافية. ينقسم هذا النوع من القافية إلى ثلاثة حروف قافية، حركات قافية وأسماء قافية.  الطريقة المستخدمة في هذا البحث وصفية نوعية. النوعي لأنه درس شعر الإعتراف لأبي نواس والوصفي لتقديم نتائج تحليل هذه القصيدة من معيار  علم العروض والقوافي.الكلمات االأساسية: علم العروض، علم القوافي، الاعتراف لأبي نواس AbstractThis study analyzes the poem of al-i’tirof by Abu Nawas in terms of Arudh and Qawafi sciences. This poem is syi’rtaqlidi (ancient poem) that is inseparable from the rules of Arudh and Qawafi. The science of Arudh and Qawafi are classical rules of rhythm that are standardized. When a poem is not in accordance with this scientific rule, then it is considered that the poem is fasid (damaged). The results of the analysis in Arudh science will produce bahar, zihaf and god used by poets in a poem. And analysis of Qawafi science will produce qafiyah forms, which are the types of qafiyah; this type of qafiyah is divided into three, including qafiyah letters, qafiyah societies, and qafiyah names. The method used in this study is descriptive qualitative. It uses qualitative method because it examines the poem of al-i’tirof by Abu Nawas and descriptive method to present the results of the analysis of this poem in terms of the science of Arudh and Qawafi.